Tantangan dan Peluang Lembaga Keuangan Syariah: Kajian Literatur - Kartika; Majid, Jamaluddin; Parmatasari, Rika Dwi Ayu (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the concepts, principles, implementation, as well as the challenges and opportunities of Islamic Financial Institutions (IFIs) in Indonesia through a qualitative literature review method. The findings show that IFIs—including Islamic banks, Islamic insurance, Islamic cooperatives, Islamic pawnshops, and Islamic finance companies—have grown significantly and contributed to the economy, particularly in financing the real sector and empowering micro, small, and medium enterprises (MSMEs). This development is supported by regulations, fatwas issued by the National Sharia Council–Indonesian Ulema Council (DSN-MUI), and the increasing public awareness of Sharia-based finance. Nevertheless, IFIs still face challenges such as low Sharia financial literacy, limited product variety, and the need for consistent Sharia compliance. On the other hand, there are substantial opportunities through product innovation, government support, and digitalization, which can enhance financial inclusion and expand service reach. Therefore, strengthening literacy, ensuring consistent Sharia compliance, and utilizing digital technology are crucial strategies to reinforce the role of IFIs in establishing a just, ethical, and sustainable financial system.